Gender-specific effects of Russia-Ukraine conflict - Evidence from South Africa - (:unkn) unknown (My University, 2024)
In this study, we use macro CGE simulation and a theoretical model combined with econometric estimations to evaluate the gender-specific impact of the Russia-Ukraine war on the South African economy. We compute individual equivalence scales and intrahousehold gender-specific allocation of the household expenditure to measure food and non-food poverty and inequality resulting from increase in crude oil, fertilizer, maize and vegetable oil prices between March 2022 and March 2023. We analyse panel survey data from the fifth round of National Income Dynamics Study 2017 and construct a static CGE model based on the PEP 1-1 model to measure changes in South African women’s employment, consumption, levels of food poverty, lower and upper poverty bounds, and income distribution. We find that the South African women are affected more by the price shock than men. Our findings are five-fold: First, Women accounted for 58 percent of the jobs lost. The demand for unskilled male labour decreased relatively more than for female labour, whereas the demand for skilled female labour fell more than their male counterparts. Second, men’s per capita food spending fell by 0.81 percent while that of women by 1 percent. Similarly, the increase in food poverty head count, depth and severity was higher among women than among men. Based on lower poverty bound, the impact on women (0.8 percentage point) was higher than that on men (0.6 percent). Third, more rural females were affected (109.2 thousand) than rural males (88.4 thousand). The increase in the depth and severity of poverty was greater among rural females (1.5 and 1.6 percentage point) than among rural males (1.4 percentage point). Fourth, Coloured and White females were affected the most in terms of food poverty with an increase of 1.3 and 0.6 percentage points, while the impact among the Black Africans and Asians was similar across genders. Finally, inequality among rural women increased more than among rural men
Keywords: African Research